2018
DOI: 10.1111/omi.12249
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide from Escherichia coli stimulates osteogenic differentiation of human periodontal ligament stem cells through Wnt/β‐catenin–induced TAZ elevation

Abstract: Human periodontal ligament stem cells (PDLSCs), a type of dental tissue–derived mesenchymal stem cells (MSCs), can be clinically applied in periodontal tissue regeneration to treat periodontitis, which is initiated and sustained by bacteria. Lipopolysaccharide (LPS), the major component of the outer membrane of gram‐negative bacteria, is a pertinent deleterious factor in the oral microenvironment. The aim of this study was to investigate the effect of LPS on the proliferation and osteogenic differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…When Wnt ligands bind the receptors LRP5/6 and Frizzled receptors, the classical Wnt/β-catenin pathway is activated, after which formation of the Wnt-fz-lrp6 complex (including Axin, APC, GSK3, and CK1) promotes the release of β-catenin [9][10][11][12][13]. Ultimately, β-catenin migrates to the nucleus, where it forms a complex with TCF/LEF to stimulate the expression of osteogenic genes, such as RUNX2, ALP, DLX5, and OCN [14,15]. Wnt3a, a ligand of Wnt, has been proven to bind BMP proteins to activate a series of downstream reactions and promote osteogenic differentiation of BMSCs [16].…”
Section: Introductionmentioning
confidence: 99%
“…When Wnt ligands bind the receptors LRP5/6 and Frizzled receptors, the classical Wnt/β-catenin pathway is activated, after which formation of the Wnt-fz-lrp6 complex (including Axin, APC, GSK3, and CK1) promotes the release of β-catenin [9][10][11][12][13]. Ultimately, β-catenin migrates to the nucleus, where it forms a complex with TCF/LEF to stimulate the expression of osteogenic genes, such as RUNX2, ALP, DLX5, and OCN [14,15]. Wnt3a, a ligand of Wnt, has been proven to bind BMP proteins to activate a series of downstream reactions and promote osteogenic differentiation of BMSCs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cdh5 controls Cldn5 by triggering its transcriptional repression via FoxO1 and β-catenin (Taddei et al, 2008). Transcriptome data in the present study revealed a significant decrease in FoxO1 expression during infection but only a slight increase in β-catenin expression, which may be related to the up-regulation of β-catenin protein levels and the activation of Wnt/β-catenin signaling by LPS (Xing et al, 2019). Moreover, Wnt/ β-catenin signaling was shown to be involved in BBB development, where its blockade decreased Cdh5 expression in primary ECs of newborn mouse brain but not in that of the adult (Hubner et al, 2018).…”
Section: Discussionsupporting
confidence: 48%
“…As discussed in the previous section, mechanosensing of substrate stiffness via YAP/TAZ regulates differentiation of MSCs into either the adipogenic or osteogenic lineage. But, contrary to what occurs in the case of osteogenesis, adipogenic differentiation is promoted on soft substrates that are nonconducive to cell adhesion and formation of FAs and stress fibers (Ji et al, 2019;Xing et al, 2019). On stiff substrates, the cytoskeletal focal adhesion protein vinculin promotes nuclear localization of TAZ, which inhibits adipogenic differentiation (Kuroda et al, 2017).…”
Section: Role Of Yap/taz In Adipogenesismentioning
confidence: 98%
“…Similarly, various pharmacologically active chemicals promote osteogenesis through activation of TAZ. These include TM-25659 (Jang et al, 2012), sodium butyrate (Fan et al, 2018), lipopolysaccharide (Xing et al, 2019), 1α,25-dihydroxyvitamin D3 (Ji et al, 2019), icariin (Wei et al, 2017;Ye et al, 2017), epicatechin gallate (ECG) (Byun et al, 2014b), phorbaketal A (Byun et al, 2012a), kaempferol (Byun et al, 2012b), and poncirin (Yoon et al, 2011).…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 99%